2021
DOI: 10.3390/agronomy11030581
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity of Soybeans (Glycine max (L.) Merr.) with Black Seed Coats and Green Cotyledons in Korean Germplasm

Abstract: Soybeans (Glycine max (L.) Merr.) with black seed coats and green cotyledons are rich in anthocyanins and chlorophylls known as functional nutrients, antioxidants and compounds with anticarcinogenic properties. Understanding the genetic diversity of germplasm is important to determine effective strategies for improving the economic traits of these soybeans. We aimed to analyze the genetic diversity of 470 soybean accessions by 6K single nucleotide polymorphic loci to determine genetic architecture of the soybe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 70 publications
2
19
1
Order By: Relevance
“…We assumed that BLG accessions could be valuable materials to identify the genes to increase seed size in soybeans. In addition, with BLG accessions, our previous study reported that most significant SNPs related to anthocyanin compositions were colocalized with the O locus, which corresponded with an anthocyanidin reductase gene and R locus, which is the R2R3 MYB transcription factor for upregulating UDP-glycose: flavonoid 3-O-glycosyltranferase (UF3GT) in black soybeans [55].…”
Section: Discussionmentioning
confidence: 94%
See 4 more Smart Citations
“…We assumed that BLG accessions could be valuable materials to identify the genes to increase seed size in soybeans. In addition, with BLG accessions, our previous study reported that most significant SNPs related to anthocyanin compositions were colocalized with the O locus, which corresponded with an anthocyanidin reductase gene and R locus, which is the R2R3 MYB transcription factor for upregulating UDP-glycose: flavonoid 3-O-glycosyltranferase (UF3GT) in black soybeans [55].…”
Section: Discussionmentioning
confidence: 94%
“…In addition, our previous study reported the analyses of population structure and PCA to reveal three clusters in 470 BLG accessions. Small-seed sizes of BLG accessions with "AA" of Gm02_8896955 were in cluster 3, whereas the ones with the "aabb" genotype belonged to cluster 2, which had relatively higher genetic diversity than clusters 1 and 3 [55]. As small-seed sizes in the "AA" genotype of Gm02_8896955 may be associated with other genes for HSW, further research like linkage analysis with a bi-parental mapping population will be required to identify genes to control seed weight with BLG accessions in "AA" genotype of Gm02_8896955.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations